EVALUASI KERJA GURU PENDIDIKAN DINIYAH TAKMILIYAH AWALIYAH (PDTA) BAITUL HAMDI KELURAHAN LIMBUNGAN KECAMATAN RUMBAI PESISIR - Nisa, Mahmudan; Achmad, Said Suhil; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research objective is 1) to find out the division of the Baitul Hamdi Education Teacher Training Diniyah Takmiliyah Awaliyah (PDTA) in Limbungan sub-district, Rumbai Pesisir District. (2) knowing the valuation of the division of labor. The research is a study evaluated with a evaluative evaluation model that uses a naturalistic qualitative approach. Evaluation is based on using the CIPP evaluation model (context, input / process, and product) of Stufflebeam. The results of the research are detailed and in the form of clauses, statements, or statements on the workings of the Teachers of Education Diniyah Takmiliyah Awaliyah (PDTA) Baitul Hamdi Limbungan sub-district, Rumbai Pesisir sub-district. The subjects of the study were all aspects related to the PDTA BaitulHamdi, namely the school, committee, 2 teachers, 2 parents, and the mosque manager in Baitul Hamam PDTA. The technique of taking data in this study is a technique of documentation, observation, and interview. Analysis in this study is data reduction, data presentation, and verification of data. The results of this study indicate that the division of PDTA teacher work.Keywords: Evaluation, Teacher's work.